A nutraceutical approach (Armolipid Plus) to reduce total and LDL cholesterol in individuals with mild to moderate dyslipidemia: Review of the clinical evidence. (February 2017) - Barrios, Vivencio; Escobar, Carlos; Cicero, Arrigo Francesco Giuseppe; Burke, David; Fasching, Peter; Banach, Maciej; Bruckert, Eric
Abstract: Compelling evidence supports the effectiveness of the reduction of total and LDL cholesterol (TC and LDL-C) in primarily preventing cardiovascular events, within the framework of life-long prevention programs mainly consisting in lifestyle changes. Pharmacological treatment should be introduced when lifestyle changes, including use of nutraceuticals, have failed. ESC/EAS guidelines list a number of nutraceutical compounds and functional foods which have been individually studied in randomized, controlled clinical trials (RCTs). To date only a proprietary formulation of three naturally occurring substances with putative complementary lipid-lowering properties − red yeast rice, policosanol and berberine – combined with folic acid, astaxanthin, and coenzyme Q10 (Armolipid Plus ® ) has been extensively investigated in several RCTs, 7 of which were placebo-controlled, 2 were ezetimibe comparators and 4 were "real life" studies comparing diet and Armolipid Plus to diet alone. The trials included mostly patients with mild to moderate dyslipidemia, treated for 6–48 weeks. The trials also included special populations and patients in whom statins were contraindicated or who could not tolerate them. Armolipid Plus has proved to be able to achieve significant reductions in TC (11–21%) and in LDL-C (15–31%) levels, which is equivalent to expectations from low dose statins. In patients intolerant to statins, who do not achieve their therapeutic target with ezetimibe, Armolipid Plus can achieve a further 10% improvement in TC and LDL-C. The safety and tolerability of Armolipid Plus were excellent, thought likely due to the intentional combination of low doses of its active ingredients: low enough not to be associated with untoward effects, but high enough to exert therapeutic effects in combination with other complementary substances. Consequently, in the event of intolerance to statins, Armolipid Plus offers an effective alternative, which is devoid of the safety risks associated with synthetic pharmacological therapy. In conclusion Armolipid Plus, in addition to dietary measures, could be a rational choice for individuals with mild to moderate hyperlipidemia and for all dyslipidemic patients in whom statins are not indicated or who cannot tolerate them.